Hearing Thresholds of Junior Secondary School Students in Kaduna Metropolis - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Communication is key to learning. Hearing is an essential part of communication without which acquisition of knowledge is, at best, very difficult. School children require a functioning auditory system for optimal educational development. In hearing impaired children educational development can be stalled should diagnosis not be done in a timely manner.Aim:The aim of the study was to evaluate the hearing threshold and determine the prevalence of hearing loss of a cohort of junior secondary school students attending schools in Kaduna North Local Government Area of Kaduna State, Nigeria.Patients and Methods:This was a cross-sectional prospective study of junior school students aged 10 years to 15 years attending selected secondary schools in Kaduna North Local Government area of Kaduna state, Nigeria. Structured questionnaire was administered to obtain relevant biodata, school type, and auditory health. Otoscopy and Pure tone audiometry were done to determine any associated ear pathology and hearing threshold levels respectively. Data obtained were recorded and analyzed using the Statistical Package for Social Sciences version 16 (SPSS Inc., Chicago, Illinois, USA). The frequency tables were generated showing the distribution of study characteristics.Results:The prevalence rate of hearing loss among junior secondary school students in Kaduna metropolis is 14.7%. Conductive hearing loss was seen in 10.3% of students and sensorineural loss in 4%.Conclusion:There is a high prevalence of hearing loss among students of junior secondary school in Kaduna especially in public schools. Other otologic pathologies like wax and foreign bodies were also noted.